PEMBENTUKAN CIVIC SKILL MAHASISWA MELALUI PEMBELAJARAN BERBASIS PROYEK PADA MATA KULIAH KEWARGANEGARAAN - Sundari Utami; Dedek Helida Pitra (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Students become agents of change who are expected to be able to become a generation of nations that are capable in various ways. Skills can be trained through the learning process, including by using the Project Based Learning (PjBL) learning model. This research uses a descriptive qualitative approach that contains explanations and descriptions in the form of narrative text as the result of the analysis. Project-based learning is carried out through civics courses, students are required to have the ability to determine problem topics, compile work steps, set work schedules, utilize monitoring, present project results through presentations, and conduct evaluations as notes for improvement. In the process of working on projects, students' civic skills are honed, to be proficient in determining actions in completing delegated tasks. Students are required to be sensitive to problems and be able to provide solutions not only in the form of theory but in the form of real actions that are realized directly so that students will have the skills that are available and able to become good citizens.